2014
DOI: 10.1038/hdy.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis reveals the ancient and recent admixture history of East African Shorthorn Zebu from Western Kenya

Abstract: The Kenyan East African zebu cattle are valuable and widely used genetic resources. Previous studies using microsatellite loci revealed the complex history of these populations with the presence of taurine and zebu genetic backgrounds. Here, we estimate at genome-wide level the genetic composition and population structure of the East African Shorthorn Zebu (EASZ) of western Kenya. A total of 548 EASZ from 20 sub-locations were genotyped using the Illumina BovineSNP50 v. 1 beadchip. STRUCTURE analysis reveals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 64 publications
15
63
0
Order By: Relevance
“…The principal component assessment agreed with previous findings, which partitioned bovine breeds into three distinct groups representing European taurines, African taurines and indicines [1418, 23, 24] (Fig. 1).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The principal component assessment agreed with previous findings, which partitioned bovine breeds into three distinct groups representing European taurines, African taurines and indicines [1418, 23, 24] (Fig. 1).…”
Section: Resultssupporting
confidence: 90%
“…Cluster analysis () and the principal component analysis were mutually supportive and highlighted the presence of three genetic backgrounds for the populations studied. The classification of the bovine populations into a triangle-like structure is well-established [1418, 23, 24]. As already mentioned, the Nguni and Afrikaner cattle were observed on the gradient between the indicines and African taurines, but more towards the African taurines, which indicates that the genomes of these breeds include more African taurine genetic background than indicine genetic background.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We detected significant differences in levels of indicine admixture among chromosomes in Ethiopian cattle. This aligns with a recent study by Mbole-Kariuki et al (2014) who detected significant differences in African taurine and Asian zebu backgrounds among chromosomes, but little variation among animals in East African shorthorn zebu populations that contained the ancient zebu and African taurine admixture. The relatively low level of variability in indicine ancestry among the Ethiopian populations supports the ancient zebu introgression into African cattle breeds.…”
Section: Discussionsupporting
confidence: 77%
“…In Kenya, Murray et al (2013) performed genomic analysis on a sample of 500 East African Shorthorn Zebu and reported average introgression levels around 2%, with 20% of calves showing levels of introgression consistent with crossing with European breeds ⩽5 generations ago. A study of the same data revealed a greater rate of European introgression in closer proximity to animal markets (Mbole-Kariuki et al, 2014). A study of African village chickens from multiple locations (Leroy et al, 2012) reported evidence of introgression in some of the countries, including Morocco and Cameroon, whereas finding negligible gene flow in some other countries such as Benin or Ghana.…”
Section: Evidence Of Crossbreeding In Developing Countriesmentioning
confidence: 99%